Using secondary image products to aid in understanding and interpretation of radar imagery - Domik, Gitta; Leberl, Franz (IGARSS'86: Remote Sensing: Today's Solutions for Tomorrow's Information Needs)

Radargrammetric Experiments with Space Shuttle SIR-B Imagery - Leberl, Franz; Domik, Gitta; Raggam, J; Cimino, J; Kobrick, M (International archives of photogrammetry and remote sensing= Archives internationales de photogrammétrie et de télédétection= Internationales Archiv der Photogrammetrie und Fernerkundung)

Case Studies Towards the Establishment of a Social History of Logic - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: Historia Mathematica 18 (1991), 400 (#18.4.67); Historical Abstracts 39A:4291.

Nichtlineare und adaptive Regelungssysteme - Böcker, Joachim; Hartmann, Irmfried; Zwanzig, Christian

Dynamics of molecular reorientations: direct determination of rotational angles from two-dimensional NMR of powders - Schmidt, Claudia; Wefing, S.; Blümich, B.; Spiess, H.W. (Chemical Physics Letters)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Eine empirische Untersuchung zu den schriftsprachlichen Leistungen türkischer Schulkinder - Beckemeyer, Rita; Tophinke, Doris (Narrative Kompetenz. Mündliche und schriftliche Wiedergabe von Erzählstrukturen durch türkische Schulkinder in außerschulischen Lerngruppen)

Geschlechtsspezifische Arbeitsteilung und technische Innovation - Neue Technologien, Frauenerwerbsarbeit und historisch-genetisches Lernen über Arbeit und Technik. - Bigga, Regine; Oberliesen, R. (Neue Technologien und technisch-ökonomische Bildung.)

ENDLESS POLARIZATION CONTROL EXPERIMENT WITH 3 ELEMENTS OF LIMITED BIREFRINGENCE RANGE - Noé, Reinhold (ELECTRONICS LETTERS)

ENDLESS POLARIZATION CONTROL IN COHERENT OPTICAL COMMUNICATIONS - Noé, Reinhold (ELECTRONICS LETTERS)

Optisches System mit einer Flüssigkristallzelle, Verfahren zu seinem Betrieb und seine Verwendung - Heppke, G.; Oestreicher, F.; Kitzerow, Heinz-Siegfried; Krumrey, M.